Riemann integral and its relation with Lebesgue integral (BIBECHANA, 2010)
This review explains the limitations of the Riemann integral and focuses on the more general concept. It has been suggested that a better route is to abandon the Riemann integral for Lebesgue integral and explained the importance of Lebesgue integral in real analysis and other fields of mathematical science. Keywords: Riemann integral; Lebesgue integral; Fourier series DOI: 10.3126/bibechana.v7i0.4051BIBECHANA 7 (2011) 83-86